2009
DOI: 10.1021/om8012162
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Control of Metallocene Backbone by Cyclopentadienyl Ring Substitution: A New Concept in Polyphosphane Ligands Evidenced by “Through-Space” Nuclear Spin−Spin Coupling. Application in Heteroaromatics Arylation by Direct C−H Activation

Abstract: The present study deals with the conformational control of the metallocene backbone within ferrocenyl polyphosphane ligands and their performance in the highly topical palladium-catalyzed heteroaromatics arylation by direct C-H activation. New substituted cyclopentadienyl rings were synthesized, which allowed the assembling of original tri-and diphosphanes. The bulky cyclopentadienyl lithium salts diphenylphosphino-3-(triphenyl)methylcyclopentadienyllithium (4) and 1,2-bis(diphenylphosphino)-4-(triphenyl)methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…A fairly good conversion of 3‐bromotoluene was obtained after 20 h (entry 9, 60% conversion) with an excellent selectivity in 5‐arylated furan. These ligandless conditions did not promote the difficult oxidative addition of 2‐bromomesitylene to palladium;32 consequently no conversion of this reagent was observed . In order to get a better knowledge of our Pd@PPy catalytic system, several experiments and characterizations were conducted during catalysis and post‐catalysis, which are described in the following sections.…”
Section: Resultsmentioning
confidence: 99%
“…A fairly good conversion of 3‐bromotoluene was obtained after 20 h (entry 9, 60% conversion) with an excellent selectivity in 5‐arylated furan. These ligandless conditions did not promote the difficult oxidative addition of 2‐bromomesitylene to palladium;32 consequently no conversion of this reagent was observed . In order to get a better knowledge of our Pd@PPy catalytic system, several experiments and characterizations were conducted during catalysis and post‐catalysis, which are described in the following sections.…”
Section: Resultsmentioning
confidence: 99%
“…However, the analogous five‐functionalized triphosphines 23–25 – with a more constraint conformation – were found active in the use of demanding haloarenes such as aryl chlorides and congested aryl bromides. The ligands 23–25 associated with Pd have shown a very good activity for arylation of highly functionalized heteroaromatics with TONs up to 1 800 (Figure ) , , . Thus, ligand 25 was mainly used for bromoarene substrates, but by using triphosphine 23 , electron‐rich, electron‐poor and multifunctionalized furans, thiophenes, pyrroles or thiazoles were arylated by various chloroarenes at 0.1–0.5 mol‐% catalyst loadings.…”
Section: Ferrocenyl Phosphinesmentioning
confidence: 99%
“…[33] Hierso and co-workers had previously described that the C-5 arylation of furan 6 with aryl bromides could be achieved using allylic palladium complex 63 with a ferrocenyl ligand as the catalyst precursor (Scheme 26). [41] More recently, the direct C-5 arylation of 2-substituted furans, thiophenes and 1-methylpyrrole with aryl chlorides was performed using the robust and electron rich PCy 3 -carbene palladium complex 64. [42,43] As shown in Scheme 27, electron-rich aryl chlorides gave better yields than did electron-deficient aryl chlorides in complex 64-catalyzed arylations of furans 6 and 7b.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 99%
“…[42] On this subject it is worth noting that in a recent discussion of the parameters that govern the activation barriers of the C À H bond in heteroarenes, Gorelsky included furan in a class (Class II) for which heteroarene-catalyst electronic interaction energies define the most reactive C À H bonds and he reported that in arylation of furan Ca À H bonds are more reactive than Cb À H bonds in the CMD process due to more negative interaction energy at the Ca site. [45] We believe it is also useful to point out that, although intermolecular direct C-2 or C-5 arylation reaction of furans are strongly favoured, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]41,42,46] successful intermolecular Pd-catalyzed C-4 arylations of furan substrates have been described. Thus, in 2009, Zhu and co-workers found that 2,5-diaryl-3-fluorofurans 65 underwent C-4 arylation with a variety of aryl bromides in NMP at 110-120 8C in the presence of KOAc as the base and a catalytic amount of PdCl 2 A C H T U N G T R E N N U N G (PPh 3 ) 2 (Scheme 28).…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 99%